The Effect of Application of Bacillus sp. and Azotobacter sp. as Plant Growth Promoter Rhizobacteria on Productivity and Yield Quality of Sweet Corn (Zea mays sacharata L.) - Purwanti, Eny Wahyuning; Waskito, Heru; Darmanto, Didik; Sa’diyyah, Iqomatus; Budianto (Jurnal Hortikultura Indonesia, 2022)
This study aims to examine the effect of the application of the bacteria Bacillus sp. and Azotobacter sp. as plant growth promotor rhizobacteria (PGPR) on the growth, productivity, and quality of sweet corn. The study used a completely randomized design single factor repeated 5 times. The treatment tested was the PGPR application which consisted of 3 levels, including without PGPR (P0), PGPR application for seed treatment (P1), and 100 ml PGPR treatment which was sprinkled on the roots every week until the 8th week (P2). The results showed that the treatment of PGPR, both seed treatment and leaking, had a significant effect on increasing cob weight without husks between 42.2 and 54.8% and stover weight between 24.2 and 30.2%. The application of PGPR also improves the quality of stover when used as feed. Increases occurred in fat content, ash content, and digestibility. PGPR also had an effect on increasing the population of decomposer arthropods, namely Collembola sp. Keywords: detrivore, growth, productivity, proximate, rhizobacteria